Global Role of Cyclic AMP Signaling in pH-Dependent Responses in Candida albicans - Jeffrey M. Hollomon (American Society for Microbiology, 2016)
ABSTRACT Candida albicans behaviors are affected by pH, an important environmental variable. Filamentous growth is a pH-responsive behavior, where alkaline conditions favor hyphal growth and acid conditions favor growth as yeast. We employed filamentous growth as a tool to study the impact of pH on the hyphal growth regulator Cyr1, and we report that downregulation of cyclic AMP (cAMP) signaling by acidic pH contributes to the inhibition of hyphal growth in minimal medium with GlcNAc. Ras1 and Cyr1 are generally required for efficient hyphal growth, and the effects of low pH on Ras1 proteolysis and GTP binding are consistent with diminished cAMP output. Active alleles of ras1 do not suppress the hyphal growth defect at low pH, while dibutyryl cAMP partially rescues filamentous growth at low pH in a cyr1 mutant. These observations are consistent with Ras1-independent downregulation of Cyr1 by low pH. We also report that extracellular pH leads to rapid and prolonged decreases in intracellular pH, and these changes may contribute to reduced cAMP signaling by reducing intracellular bicarbonate pools. Transcriptomics analyses found that the loss of Cyr1 at either acidic or neutral pH leads to increases in transcripts involved in carbohydrate catabolism and protein translation and glycosylation and decreases in transcripts involved in oxidative metabolism, fluconazole transport, metal transport, and biofilm formation. Other pathways were modulated in pH-dependent ways. Our findings indicate that cAMP has a global role in pH-dependent responses, and this effect is mediated, at least in part, through Cyr1 in a Ras1-independent fashion. IMPORTANCE Candida albicans is a human commensal and the causative agent of candidiasis, a potentially invasive and life-threatening infection. C. albicans experiences wide changes in pH during both benign commensalism (a common condition) and pathogenesis, and its morphology changes in response to this stimulus. Neutral pH is considered an activator of hyphal growth through Rim101, but the effect of low pH on other morphology-related pathways has not been extensively studied. We sought to determine the role of cyclic AMP signaling, a central regulator of morphology, in the sensing of pH. In addition, we asked broadly what cellular processes were altered by pH in both the presence and absence of this important signal integration system. We concluded that cAMP signaling is impacted by pH and that cAMP broadly impacts C. albicans physiology in both pH-dependent and -independent ways.